Prototype Resusitasi Jantung Paru (RJP) menggunakan Motor Nema 23 dan Sensor Detak Jantung untuk Memudahkan Media Interface - Maili, Ramadoni; Jufrizel, Jufrizel; Ullah, Aulia; Maria, Putut Son (Universitas Budi Darma, 2024)
The growth of technology has an important role in supporting medical equipment facilities, especially for tools for providing compression or cardiopulmonary resuscitation (CPR). CPR is a first aid measure for victims of sudden cardiac arrest in which cardiac compression is carried out for 4 cycles, each cycle consisting of 30 compressions. CPR given manually can endanger the victim due to certain factors such as insufficient or excessive pressure applied. So that the above can be realized, a tool is needed that can make it easier for someone to check their heart rate on their skin quickly and effectively. The MAX30102 sensor is a sensor that can calculate heart rate. This research aims to create an optimal automatic cardiopulmonary resuscitation device to help victims continue to breathe. This RJP tool uses a Nema 23 stepper motor as the driving motor, the motor driver uses a TB6600 driver as the motor controller. During testing, 1 minute produced 103 compressions and 30 compressions in 18 seconds. The torque strength of the stepper motor is only capable of lifting a load of 7 kg, the torque produced is 2.06 Nm. This research also uses sensors to detect heartbeats. This allows the device user to monitor the patient's heartbeat while undergoing RPJ.